Etiologies of chronic cough in adult patients: Is it hard to be diagnosed? - Abdul-Razaq, Mohammad Yahya; Sultan, Kassim M.; Muhammed, Shakir M. (AL-Kindy College Medical Journal, 2011)
Background: Chronic cough is often the keysymptom not only of chronic pulmonary diseasesbut for other important extrapulmonarypathologies, in particular upper airway andgastrointestinal diseases.Objective: This study was designed todetermine the etiology of chronic cough and theusefulness of the available diagnostic tests inreaching its causes.Methods: One hundred patients presenting withchronic cough at Baghdad Teaching HospitalOutpatient Clinic were enrolled in this study. Thepatients underwent a full clinical interview,physical examination with indicated diagnostictest(s) (such as chest x ray, bronchoscope, PFT,GIT study, sinus X ray or CT).Results: An etiology of chronic cough wasdetermined in 93% of the patients. Post nasal dripis the leading cause of chronic cough reported in31% of the patient, while asthma gastroesophagealreflux disease, and chronic bronchitisseen in (26, 20, and 6 % respectively).The diagnosis of chronic cough can be reached bycomprehensive history, proper physicalexamination, and chest X ray findings in 66 %patients, further more sophisticated and invasivetests like: PFT, upper GIT study , expectoratedsputum examination (AFB, Gram staining,cytology), fibrooptic bronchoscope, and full ENTevaluation including sinuses X ray or sinuses CTscanning, are need in the rest.Conclusion: The etiology of chronic cough canoften be diagnosed safely with a simple initialevaluation (history, physical examination andchest X-ray). Postnasal drip, asthma andgastroesophageal reflux disease account for theetiology in more than three quarter of the patients.